Current Trends of application of Activity Based Costing (ABC): a Review (Global Journal of Management and Business Research, 2013)
Activity-based costing (ABC) is a method for determining true costs. Though ABC is a relatively recent innovation in cost accounting, it is rapidly being adopted by companies across many industries, within government and other organizations like institutions, finance or service sectors. In the light of current practices, this paper emphasizes to understand the need and importance of ABC costing in the organizations. This is coupled with management methods, an extensive range of uses, empowering utilization of ABC information for a wide variety of company functions and operations such as process analysis, strategy support and time-based accounting, monitoring wastage and quality along with productivity management.
Keywords: activity based costing; value added activity; cost drivers